Cost-effectiveness of radiofrequency catheter ablation for the treatment of atrial fibrillation in the United Kingdom. Issue 7 (18th December 2008) - McKenna, C; Palmer, S; Rodgers, M; Chambers, D; Hawkins, N; Golder, S; Van Hout, S; Pepper, C; Todd, D; Woolacott, N
Abstract : Objective: To assess the cost-effectiveness of radiofrequency catheter ablation (RFCA) compared with anti-arrhythmic drug (AAD) therapy for the treatment of atrial fibrillation (AF) from the perspective of the UK NHS. Design: Bayesian evidence synthesis and decision analytical model. Methods: A systematic review and meta-analysis was conducted and Bayesian statistical methods used to synthesise the effectiveness evidence from randomised control trials. A decision analytical model was developed to assess the costs and consequences associated with the primary outcome of the trials over a lifetime time horizon. Main outcome measure: Costs from a health service perspective and outcomes measured as quality-adjusted life years (QALYs). Results: The incremental cost-effectiveness ratio of RFCA varied between £7763 and £7910 for each additional QALY according to baseline risk of stroke, with a probability of being cost-effective from 0.98 to 0.99 for a cost-effectiveness threshold of £20 000. Results were sensitive to the duration of quality of life benefits from treatment. Conclusions: RFCA is potentially cost-effective for the treatment of paroxysmal AF in patients' predominantly refractory to AAD therapy provided the quality-of-life benefits from treatment are maintained for more than 5 years. These findings remain subject to limitations in the existing evidence regarding the nature of life benefits and the prognostic importance of restoring normal sinus rhythm conferred using RFCA.